2013
DOI: 10.1248/cpb.c12-01046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Xanthine Derivatives on Dipeptidyl Peptidase 4

Abstract: A series of xanthine derivatives in which a methylene was inserted at position 8 of xanthine scaffold was synthesized and evaluated as inhibitors of dipeptidyl peptidase 4 (DPP-4) for the treatment of type 2 diabetes. As the results of structure-activity relationship (SAR) study of the series, the compounds with 4-methyl-quinazoline-2-yl-methyl group at N-1 position and 2-aminoethylaminomethyl group gave better activities. Compounds H4 and H9 showed good DPP-4 inhibition and more than 100-fold selectivity over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…98 Xanthine-based compounds were also developed, resulting in compounds with 1−30 μM IC 50 values and acceptable selectivity versus the other peptidases of the DPP IV family. 99 Therefore, docking-based approaches resulted in DPP IV inhibitors that were very selective for this enzyme compared to DPP-8 and DPP-9 but with low inhibition potency. However, it can be postulated that pursuing these lead molecules may result in potentially interesting therapeutics for further clinical development.…”
Section: ■ More Recent Dpp IV Inhibitors Under Developmentmentioning
confidence: 99%
“…98 Xanthine-based compounds were also developed, resulting in compounds with 1−30 μM IC 50 values and acceptable selectivity versus the other peptidases of the DPP IV family. 99 Therefore, docking-based approaches resulted in DPP IV inhibitors that were very selective for this enzyme compared to DPP-8 and DPP-9 but with low inhibition potency. However, it can be postulated that pursuing these lead molecules may result in potentially interesting therapeutics for further clinical development.…”
Section: ■ More Recent Dpp IV Inhibitors Under Developmentmentioning
confidence: 99%
“…It has been shown that linagliptin, DPP-4 inhibitor with xanthine-based structure ( Figure 2) and reported IC50 value of ~ 1 nM (13)(14)(15)(16), at the oral dose of 5 mg/kg for 7 days normalized increased serum XO activity in septic rats (17). Additionally, linagliptin exerted an inhibitory effect on the activity of XO in vitro and in human serum derived from the healthy volunteer in a concentration-dependent manner up to 1 mM, as well as lowered uric acid levels in plasma of diabetic patients at the oral dose of 5 mg once daily for 24 weeks (18).…”
Section: Linagliptin Dipeptidyl Peptidase-4 and Xanthine Oxidase Inhmentioning
confidence: 99%
“…Some DPP-4 inhibitors (13)(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) have been derived from a xanthine scaffold, similar to the structure of linagliptin (Table 1, Figure 3). 61 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 61 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 CH3 ...…”
Section: Overview Of Purine-based Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Many synthetic analogs of alogliptin by replacing the cyanobenzyl group with the butynyl group have been synthesized and tested as selective DPP‐4 inhibitors . Additionally, quinazolines , pyridopyrimidinedione , pyrazolopyrimidinones , and pyrimidine as DPP‐IV inhibitors are of particular interest in this field. Furthermore, various quinazoline, thiazoline, and quinazoline clubbed thiazoline analogues proved to be effective antidiabetic agents (Fig.…”
Section: Introductionmentioning
confidence: 99%